2018
DOI: 10.1002/2017gh000101
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Rotavirus Diarrheal Risk Due to Hydroclimatic Extremes Over South Asia: Prospects of Satellite‐Based Observations in Detecting Outbreaks

Abstract: Rotavirus is the most common cause of diarrheal disease among children under 5. Especially in South Asia, rotavirus remains the leading cause of mortality in children due to diarrhea. As climatic extremes and safe water availability significantly influence diarrheal disease impacts in human populations, hydroclimatic information can be a potential tool for disease preparedness. In this study, we conducted a multivariate temporal and spatial assessment of 34 climate indices calculated from ground and satellite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 53 publications
0
16
0
3
Order By: Relevance
“…Furthermore, that the absolute effect of precipitation was barely significant and that this variable was excluded from the final absolute effect model by stepwise selection might be due to these two competing pathways (the runoff effect versus the concentration effect 4 ) influencing rotavirus transmission in opposite directions in the rainy season compared with drier times of the year, which could cancel each other out unless seasonality is adjusted for. Recent studies have found that these opposing effects, each taking over from the other as rainy seasons give way to drier periods, are a notable feature of rotavirus epidemiology, particularly in southeast Asia 28, 30. The absence of an interaction identified between precipitation and any other hydrometeorological variable is consistent with this variable operating via a separate pathway.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, that the absolute effect of precipitation was barely significant and that this variable was excluded from the final absolute effect model by stepwise selection might be due to these two competing pathways (the runoff effect versus the concentration effect 4 ) influencing rotavirus transmission in opposite directions in the rainy season compared with drier times of the year, which could cancel each other out unless seasonality is adjusted for. Recent studies have found that these opposing effects, each taking over from the other as rainy seasons give way to drier periods, are a notable feature of rotavirus epidemiology, particularly in southeast Asia 28, 30. The absence of an interaction identified between precipitation and any other hydrometeorological variable is consistent with this variable operating via a separate pathway.…”
Section: Discussionmentioning
confidence: 91%
“…While the primary routes of rotavirus transmission involve direct person-to-person transmission or contact with contaminated surfaces and fomites, the importance of waterborne transmission is gaining salience [54]. Flooding in the Solomon Islands in 2014 caused a nationwide outbreak of rotavirus diarrhea [55], while recent evidence from Bangladesh have linked both particular precipitation events-notably the 2007 flood [17]-and rainy days in general to upticks in rotavirus [56]. Previous analyses of data from the South Asian MAL-ED sites have identified secondary seasonal peaks in rotavirus coinciding with the annual monsoon season [39,57] and recent findings of a protective effect of drinking water from tube wells are consistent with these results, since these water supply systems draw upon deeper groundwater reserves that are better protected from flood-related contamination than sources nearer to the surface [58].…”
Section: Discussionmentioning
confidence: 99%
“…Ротавирусной инфекцией заболевает практически каждый ребенок в возрасте до 5 лет, она является причиной водянистой диареи у детей младшего возраста во всем мире 3 . В странах с низким доходом населения первичное заражение детей младше пяти лет ротавирусной инфекцией наблюдается в возрасте от 6 до 9 месяцев (80 % заболеваемости среди детей до 1 года).…”
unclassified
“…В странах Северного полушария с умеренным климатом выражена зимняя сезонность заболеваемости инфекцией. В регионах Азии, Африки и Латинской Америки эпидемиология ротавирусной инфекции характеризуется высокой степенью передачи в течение всего года, при этом наблюдаются один или два периода подъема циркуляции ротавируса в местностях, где на климат влияют муссоны [3]. На эпидемический процесс определенное действие оказывает значительная разница между ночной и дневной температурами, а также количество дождливых дней [3].…”
unclassified
See 1 more Smart Citation